Pendidikan Islam Di Kesultanan Aceh Ulama, Meunasah, Rangkang Serta Pesantren Dan Pembaharuannya (Modernisasi Pesantren) Arah Dan Implikasi, Kasus Gontor: Indonesia - Zihnil Afif; Devi Syukri Azhari; Zulmuqim Zulmuqim; Duski Samad (Jurusan Pendidikan IPS FKIP UNJA, 2023)
The personality and behavior of Rasulullah SAW. Is a role model for Muslims in all aspects of life. Because the main function of his profession is none other than as an educator of the people, his tradition in educating the people is of great concern to the Muslims to be carried on from generation to generation, from one country to another. This source is clear, firm, pure, and originality is maintained so that Islamic education always gets clear bases and objectives, even detailed and subtle operational procedures, no matter how far the distance and time and space are between the role model and the implementers of Islamic education. the. Bumi Nangroe Aceh Darussalam is proof of the statement above. Islam entered, took root, and developed in an area known as the Veranda of Mecca, even with the physical strength of the soldiers, but through the power of the pen and the words of the teachers and educators. The tradition of Islamic education which was planted by the pioneers of the arrival of Islam to Aceh continues to be cared for and maintained by the sons of Aceh, both as individuals and through educational institutions. Gontor Islamic Boarding School is one of the oldest educational institutions in Indonesia and was founded on Islamic principles. The Islamic doctrines learned and disseminated by the Gontor Islamic Boarding School were eventually firmly embedded in Indonesian Islamic culture. Without pesantren, it would be impossible to promote respect for Islamic cultural traditions. Gontor Islamic boarding schools are expected to develop into centers of Islamic culture and civilization in Indonesia. In this case, First, the Kiai is the main element of the pesantren, teaching religious principles so that they can emphasize their distinctive strategy for implementing Islamic teachings; the second is the santri, which is very important in pesantren because it shows how far Islamic education has come and how well it is taught; the third is the mosque, which functions as a place of prayer and religious teaching. This requires a special room, the complexity of which varies according to the mission of the pesantren. fourth is Madrasah, namely the place where the teaching and learning process takes place; finally the fifth is a place to live, which is called a hostel or cottage; and these five things are all needed in the gontor pesantren.